Prediction of Symptomatic Severe Acute Respiratory Syndrome Coronavirus 2 Infection by Quantitative Digital Polymerase Chain Reaction Normalized to International Units. (21st September 2022) - Hijano, Diego R; Gu, Zhengming; Brazelton, Jessica; Zhu, Haiqing; Suganda, Sri; Glasgow, Heather L; Darji, Himani; Tang, Li; Fabrizio, Thomas P; Allison, Kim J; Allen, E Kaitlynn; ,; et al.
Abstract: Although numerous studies have evaluated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection using cycle threshold (Ct) values as a surrogate of viral ribonucleic acid (RNA) load, few studies have used standardized, quantitative methods. We validated a quantitative SARS-CoV-2 digital polymerase chain reaction assay normalized to World Health Organization International Units and correlated viral RNA load with symptoms and disease severity. Abstract : Studies have evaluated SARS-CoV-2 infection using Cycle Thresholds (Ct) values as a surrogate of viral RNA load. We validated a quantitative SARS-CoV-2 digital PCR assay normalized to WHO International Units and correlated viral RNA load with symptoms and disease severity.